The Effect of Price, Product Quality and Service Quality of Design Services on Customer Satisfaction at The Berkah Gemilang Banner Shop Medan - Muhammad Ilham Shukri; Roro Rian Agustian (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyse the effect of price, product quality, and service quality of design service on costumer satisfaction at Berkah Gemialng Medan Banner Shop. This study uses a quantitative approach with a survey methode through distributing questionnaires to 62 respondents who are consumers of the store. The sampling technique used simple random sampling. The research instrument has been tested for validity and reliability, with the result that all questionnaire items are declared valid and reliable ( Cronbach`s Alpha 0.70). The results of multiple linear regression analysis show that the variables of price, product quality, and service quality of design service partially and simultaneously have a significant effect on costmer satisfaction. The coefficient of determination (R2) of 0.679 indicates that the model is able to explain varitions in costumer satisfaction well. This study contibutes to the development of managerial strategies, especially in increasing costumer satisfaction in the printing industry.